The Effect of Investment Portfolio on Investment Returns in Islamic Insurance Companies - Aprilianto, Fitrian; Mahdi, Fadilla Muhammad (Universitas Al-Qolam Malang, 2025)
The importance of investment portfolios in Islamic insurance companies is fundamental to obtaining optimal returns. A well-diversified portfolio can help companies manage their risks and optimize their returns. By opting for appropriate investment instruments, the company can enhance liquidity, stability, and asset growth, which in turn will provide greater benefits to insurance participants. This study focuses on investment portfolio variables, given the important role of investment in Islamic insurance companies. Therefore, this study aims to determine the effect of deposit variables, Islamic stocks, corporate sukuk, State Sharia Securities (SBSN), Islamic mutual funds, direct investment, and other investments on the investment returns of Islamic insurance companies. This study uses a quantitative research approach; it uses the type of data, which is secondary data obtained from the Financial Services Authority (OJK), starting from January 2014-December 2022. The method of analysis used in this research is multiple linear regression analysis. The results showed that the variable deposits, Sharia stocks, corporate sukuk, Sharia mutual funds, direct participation, and other investments had a significant effect, while the SBSN variable was not significant.